Pyometra and Polycystic Ovaries in Female Dogs - Duarte, Luz; Sánchez, Favio; Ortega, Carolina (Spei Domus, 2014)
Introduction: the objective of this paper was to find a connection between cystic endometrial hyperplasia (ceh)-pyometra and polycystic ovaries through observation and macroscopic measurements of canine uterus in subjects with pyometra that underwent hysterectomy to solve the problem. Methods: such organs were obtained from two clinics in Bucaramanga. All the found variables were registered in Excel 2003 and analyzed with Epi Info 7, so as to develop an invariable descriptive statistics analysis, a contingency table and a Fisher’s exact test. The pyometra and ceh were correlated with polycystic ovaries (po). Statistically, there was no relation between such variables, (p> 0,05). Results : existence of ceh was 87.10% of the total cases in respect of the polycystic ovaries frequency, since only 32.26% was not found to be statistically related. Literature reports that the etiology of the ceh complex is caused by an increase in estrogenic hormones in the diestrus phase [1] and such hormone imbalance is in turn responsible for the development of polycystic ovaries. Conclusions: it would be thus appropriate to conduct studies with the hormone measurements in canine subjects with pyometra and verify the macroscopic findings of such cases.